Food Estate Kalimantan Tengah: Tinjauan Sosial, Ekonomi dan Lingkungan pada Kabupaten Kapuas dan Pulang Pisau - Husnatarina, Fitria; Suherman, Suherman; Ompusunggu, Dicky Perwira; Nasrida, Muhammad Farras; Rakhmawati, Dewi (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyse the social, economic and environmental impacts of the Food Estate programme in Kapuas and Pulang Pisau districts, and provide recommendations for more sustainable development. The research approach used was mixed methods, combining qualitative data from in-depth interviews and focus group discussions (FGDs) with quantitative data from surveys and secondary data. The results show that the programme has had a positive impact on increasing farmers' productivity and income, as well as opening up opportunities for youth involvement in agriculture. However, there are challenges in market access, technology adaptation for older farmers, and potential environmental degradation, especially in wetland areas. This study recommends improving market access and downstream infrastructure, more intensive technology assistance, and conservation strategies to maintain ecosystem balance. These recommendations are expected to improve the sustainability of the Food Estate programme and provide long-term benefits to local communities.